The Influence of Virtual Reality on Consumer Decision Making through a Neuromarketing Perspective - Sjukun (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Consumer decisions are not entirely rational, but are influenced by emotions, intuition, and unconscious biases. Neuromarketing approaches provide new ways to uncover previously undetected psychological mechanisms behind consumer decisions. This study aims to analyze the synergistic impact of neuromarketing devices and virtual reality experiences on consumer decision-making, with particular emphasis on the mediating role of consumer emotional engagement. This research method uses a quantitative research design. Data were collected from 100 university students in Medan City, Indonesia, who are active Shopee users, through a structured questionnaire. Data analysis was conducted using Smart PLS. The results revealed a significant direct effect of neuromarketing tools on emotional engagement and consumer decision-making, as well as a strong influence of virtual reality experiences on emotional engagement. Although the direct effect of virtual reality on decision-making was not significant, emotional engagement significantly mediated the relationship between neuromarketing tools and virtual reality experiences on consumer decision-making. These findings underscore the important role of emotional engagement as a channel for the effectiveness of advanced marketing technologies.